Spatiotemporal Gait Variability in Children Aged 2 to 10 Decreases throughout Pre-Adolescence - Bryon C. Applequist; Zachary L. Motz; Anastasia Kyvelidou (Biomechanics, 2023)
Background: Children’s gait is traditionally understood to mature as young as three years old through pre-adolescence. Studies looking at gait biomechanics suggest that gait matures around three years old, while studies investigating gait variability propose a much later maturation. The studies that have examined children’s gait variability did so while the children walked around a track or down hallways that created a discontinuous gait, potentially affecting the measures of variability and the efficacy of the results. Purpose: Therefore, the purpose of our study was to investigate the development of gait dynamics and gait variability in children in a more continuous fashion, in this case, by walking on a treadmill. Methods: To accomplish this, we included four age groups of children, ranging 2–10 years old, walking on a treadmill for at least three minutes while stride time and stride length were collected. Stride time and stride length’s variability was then analyzed using linear (mean, standard deviation, coefficient of variation) and nonlinear (sample entropy, detrended fluctuation analysis) measures across the varying ages of our participants. Results: Interestingly, both the linear and nonlinear variabilities of the stride time and stride length measures decreased as the groups of children got older. Specifically, CV ST (2–3 (9.3 ± 4%), 8–10 (3.6 ± 0.7%), p < 0.05) and CV SL (2–3 (11.4 ± 3%), 8–10 (4.6 ± 1%), p < 0.05) were our strongest linear measures, and DFA α ST (2–3 (0.97 ± 0.12), 8–10 (0.82 ± 0.10), p < 0.05) and DFA α SL (2–3 (0.91 ± 0.04), 8–10 (0.81 ± 0.03), p < 0.05) were our strongest nonlinear measures, particularly between the youngest and oldest groups. This trend of variability decreasing with age suggests that as children’s gait matures, their gait becomes more stable and reliable. Significance: Our study rejects the notion that children’s gait is mature by the age of three, as some would suggest. By analyzing the variability of stride time and stride length, we can see that even later into childhood, children’s gait continues to change and evolve.